The View from Here : Eureka, Colorado #1 - Myers, Cindy (New York : Kensington Books, 2012)
When newly divorced Maggie Carter inherits a gold mine from the father she never knew, she leaves Houston and travels to the small town of Eureka, Colorado. There, she hopes to solve the mystery of the man who abandoned the family when she was three. In Eureka, Maggie meets people who touch her life in different ways, bitter librarian Cassie Wynock, town mayor Lucille Theriot; and Jameso Clark, whose love-hate relationship with her father intrigues Maggie, and whose attraction for her she finds both frightening and exhilarating. As Maggie confronts the sins of her father and the mistakes of her own past she learns to look at life differently and discovers it can take a village or one small mountain town to heal a heart.
"Kensington fiction"--Spine.
Keywords: Fathers and daughters -- Fiction; Inheritance and succession -- Fiction; Gold mines and mining -- Fiction; Life change events -- Fiction; Colorado -- Fiction; Adventure fiction; Western fiction